Development and evaluation of a head-controlled human-computer interface with mouse-like functions for physically disabled users (Clinics, 2009)
OBJECTIVES: The objectives of this study were to develop a pointing device controlled by head movement that had the same functions as a conventional mouse and to evaluate the performance of the proposed device when operated by quadriplegic users. METHODS: Ten individuals with cervical spinal cord injury participated in functional evaluations of the developed pointing device. The device consisted of a video camera, computer software, and a target attached to the front part of a cap, which was placed on the user's head. The software captured images of the target coming from the video camera and processed them with the aim of determining the displacement from the center of the target and correlating this with the movement of the computer cursor. Evaluation of the interaction between each user and the proposed device was carried out using 24 multidirectional tests with two degrees of difficulty. RESULTS: According to the parameters of mean throughput and movement time, no statistically significant differences were observed between the repetitions of the tests for either of the studied levels of difficulty. CONCLUSIONS: The developed pointing device adequately emulates the movement functions of the computer cursor. It is easy to use and can be learned quickly when operated by quadriplegic individuals.